X-Ray Co-Crystal Structure Guides the Way to Subnanomolar Competitive Ecto-5 '-Nucleotidase (CD73) Inhibitors for Cancer Immunotherapy - Sanjay Bhattarai; Jan Pippel; Anne Meyer; Marianne Freundlieb; Constanze Schmies; Aliaa Abdelrahman; Amelie Fiene; Sang-Yong Lee; Herbert Zimmermann; Ali El-Tayeb; Gennady G. Yegutkin; Norbert Sträter; et al. (WILEY, 2022)
Ecto-5'-nucleotidase (CD73, EC 3.1.3.5) catalyzes the extracellular hydrolysis of AMP yielding adenosine, which induces immunosuppression, angiogenesis, metastasis, and proliferation of cancer cells. CD73 inhibition is therefore proposed as a novel strategy for cancer (immuno)therapy, and CD73 antibodies are currently undergoing clinical trials. Despite considerable efforts, the development of small molecule CD73 inhibitors has met with limited success. To develop a suitable drug candidate, a high resolution (2.05 degrees A) co-crystal structure of the CD73 inhibitor PSB-12379, a nucleotide analogue, in complex with human CD73 is determined. This allows the rational design and development of a novel inhibitor (PSB-12489) with subnanomolar inhibitory potency toward human and rat CD73, high selectivity, as well as high metabolic stability. A co-crystal structure of PSB-12489 with CD73 (1.85 degrees A) reveals the interactions responsible for increased potency. PSB-12489 is the most potent CD73 inhibitor to date representing a powerful tool compound and novel lead structure.